Promosi Pencegahan Perilaku Berisiko Penyalahgunaan Napza pada Remaja dengan Media Video Kearifan Lokal Maja Labo Dahu dan Poster - Ahmad; Sukmawati; Fadlurrahmi (CV. CENDIKIA JENIUS INDONESIA, 2026)
This community service activity aimed to improve adolescents’ knowledge in preventing risky behaviors related to drug abuse through health promotion based on the local wisdom of Maja Labo Dahu. The implementation method employed an implementation–evaluation approach conducted in eight schools in Palibelo District, Bima Regency, in collaboration with the Palibelo Primary Health Center (Youth-Friendly Health Services/PKPR). The intervention consisted of educational video screenings integrating local cultural values, reinforcement of key messages using posters as cues to action, interactive discussions, and training on refusal skills to resist drug use. Evaluation was carried out using a pre-test and post-test design to assess changes in adolescents’ knowledge. A total of 30 respondents participated in the activity. The results demonstrated a substantial improvement in knowledge, with the proportion of respondents in the “good” knowledge category increasing from 10.0% before the intervention to 83.3% after the intervention, while the “poor” category decreased from 63.3% to 3.3%. In conclusion, health promotion using video and poster media integrated with the local wisdom of Maja Labo Dahu is effective as a primary prevention strategy to enhance drug literacy among adolescents.